Tingkat Kepuasan Konsumen terhadap Pembelian pada E-Commerce Selama Masa Pandemi Covid-19 - Cholilah, Indah Roziah (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2023)
The concept of trading through electronic commerce (e-commerce) is a business model conducted through social media, where companies and individuals buy and sell goods or products electronically. People utilize online shopping to avoid exposure to the coronavirus (COVID-19) virus. In order to ensure customer satisfaction with e-commerce, businesses are expected to provide the best quality of service. Customer satisfaction is the emotional response to the experience of using the purchased service or product. This condition is demonstrated by the increased usage of e-commerce systems, repurchasing products, loyalty, and word-of-mouth referrals to encourage others to use e-commerce. This study aims to determine the level of customer satisfaction in using e-commerce during the COVID-19 pandemic. The research utilizes a mixed-method approach with a sequential explanatory strategy, which involves gathering quantitative data followed by in-depth exploration of customer satisfaction levels through qualitative interviews. The research subjects consist of 92 individuals experienced in conducting transactions through e-commerce. Random sampling is used for sample selection, and data collection is conducted through interviews and a satisfaction level measurement tool distributed via Google Forms. The results of the research indicate that 17.4% of customers feel very satisfied, 40.2% feel satisfied, 37% feel moderately satisfied, 4.3% feel dissatisfied, and 1.1% feel very dissatisfied. Furthermore, additional information is obtained from the statements of 66 individuals, or approximately 78% of the customers, who believe that purchasing goods using e-commerce services helps reduce crowded activities that can accelerate the spread of the COVID-19 virus.